Learning al-Qur'an with the Syafi'i Method for Improving Reading Skill - Alhamuddin, Alhamuddin; Surbiyantoro, Eko; Erlangga, Revan Dwi (KnE Social Sciences, 2023)
The objective of this service is to enhance participants’ potential in reading the Qur’an, specifically in terms of the rules of tajweed and makharijul khuruf. The service employs a combination of lectures and direct practice, utilizing the Syafi’i Method for Qur’an recitation. The outcomes of this service are as follows: (a) Participants continue to face difficulties in reading and comprehending the Qur’an due to the lack of innovative approaches in Qur’an education by teachers, as well as inadequate infrastructure to support the advancement of Qur’an learning in mosques. (b) The effectiveness of utilizing the Syafi’i Method in Qur’an education significantly influences the development of participants’ Qur’an reading skills. Keywords: quality improvement, Syafi’i Method, learning the Qur’an